Rehydration strategies before and after exercise - Burke, L. M. (Australian Journal of Nutrition & Dietetics, 1996)
Optimal hydration involves fluid intake strategies before, during and after exercise sessions. In most situations sweat losses during exercise exceed the opportunities for fluid replacement during the activity. Therefore, it is important that residual levels of hypohydration are corrected during post-exercise recovery, particularly in preparation for future exercise sessions. Athletes should aim to start each exercise session in fluid balance. At special risk are those athletes who dehydrate to `make weight` in weight division sports. Hyperhydration before exercise may be useful where fluid losses during exercise are likely to greatly exceed the potential for fluid intake. However, more research is needed before special techniques such as hyperhydration with glycerol can be universally recommended. Rehydration after exercise requires a specific fluid intake plan since thirst and voluntary intake will not provide for full restoration of sweat losses in the acute phase (zero to six hours) of recovery. Steps should be taken to ensure that a supply of palatable drinks is available after exercise. Sweetened drinks are generally preferred and may help with carbohydrate intake goals. Replacement of sodium lost in sweat is important in maximising the retention of ingested fluids. A sodium content of 50 to 90mmol/L may be necessary for optimal rehydration. However commercial sports drinks are formulated with a more moderate sodium content (10-25mmol/L). It may be necessary to consume 150% of fluid losses to allow for complete fluid restoration. Beverages containing caffeine and alcohol are not ideal rehydration fluids since they promote an increased rate of diuresis.